2006
DOI: 10.1021/jp053915e
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrates of Argon and Methane Synthesized at High Pressures:  Composition, Thermal Expansion, and Self-Preservation

Abstract: For the first time, the compositions of argon and methane high-pressure gas hydrates have been directly determined. The studied samples of the gas hydrates were prepared under high-pressure conditions and quenched at 77 K. The composition of the argon hydrate (structure H, stable at 460-770 MPa) was found to be Ar.(3.27 +/- 0.17)H(2)O. This result shows a good agreement with the refinement of the argon hydrate structure using neutron powder diffraction data and helps to rationalize the evolution of hydrate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 44 publications
7
66
0
2
Order By: Relevance
“…This qualitative finding agrees with the results from Molecular Dynamics simulations of Alavi et al [22]. Our GCMC results regarding the number of the enclathrated argon molecules in each type of cavity are in very good agreement with the available experimental data [18,21]. In specific, we estimate that the composition of the sH hydrate, at 760 MPa, is Ar·3.4H 2 O (all large cavities occupied by five Ar molecules) which is exactly the same with the measurements of Manakov et al [21] while Inerbaev et al reported a slightly higher Ar content in the hydrate (Ar·3.27H 2 O).…”
Section: Sh Argon Hydratesupporting
confidence: 92%
See 3 more Smart Citations
“…This qualitative finding agrees with the results from Molecular Dynamics simulations of Alavi et al [22]. Our GCMC results regarding the number of the enclathrated argon molecules in each type of cavity are in very good agreement with the available experimental data [18,21]. In specific, we estimate that the composition of the sH hydrate, at 760 MPa, is Ar·3.4H 2 O (all large cavities occupied by five Ar molecules) which is exactly the same with the measurements of Manakov et al [21] while Inerbaev et al reported a slightly higher Ar content in the hydrate (Ar·3.27H 2 O).…”
Section: Sh Argon Hydratesupporting
confidence: 92%
“…Grand Canonical Monte Carlo simulations were performed for sII and sH hydrates of argon that were identified to exhibit multiple occupancies of the large cages of the hydrate crystal [18][19][20][21][22][23]. All runs were carried out with a lattice parameter of 17.1423 Å [41].…”
Section: Hydrate Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it was suggested that the nature of the ice crystals and the interaction between guest molecules and H 2 O molecules [6] both affect anomalous preservation phenomena for gas hydrates. We think that the gas hydrates which show self-preservation phenomena by the temperature-ramping method in earlier studies, [6,23] such as N 2 ,O 2 , Ar, and H 2 hydrate, will also show anomalous preservation by the rapid pressure-release method. Preservation phenomena for hydrates of these binary gas systems are also expected.…”
Section: Anomalous Preservation Of Ch 4 Hydrate and Its Dependence Onmentioning
confidence: 94%